The Crisis of Education in Modern Societies according to Ali Izet Begovic - Abdulrazzaq , Emad (Nama Journal of Islamic Sciences and Humanities, 2023)
This research deals with the education crisis in modern societies from Ali Izet Begovic’s point of view. In the research, he gave an account of his life and writings, the Islamic renaissance and its starting points, the Islamic awakening, the Islamic system, and education. The research stressed the importance of reconsidering technical and classical education because it has an effective and pivotal role in the advancement and development of nations, and it is also the cause of civilization. Attention must also be paid to educating young people from an early age not to surrender or submiss. Rather, the spirit of criticism and challenge must be instilled within them. Moreover, their creative spirit must be developed and their abilities unleashed. Education is the heart and essence of the Islamic religion, which achieves the highest values and ideals.